Global stocks and capacity of mineral-associated soil organic carbon - Georgiou, Katerina; Jackson, Robert B.; Vindušková, Olga; Abramoff, Rose Z.; Ahlström, Anders; Feng, Wenting; Harden, Jennifer W.; Pellegrini, Adam F. A.; Polley, H. Wayne; Soong, Jennifer L.; Riley, William J.; Torn, Margaret S. (Nature communications, 2022)
Soil is the largest terrestrial reservoir of organic carbon and is central for climate change mitigation and carbon-climate feedbacks. Chemical and physical associations of soil carbon with minerals play a critical role in carbon storage, but the amount and global capacity for storage in this form remain unquantified. Here, we produce spatially-resolved global estimates of mineral-associated organic carbon stocks and carbon-storage capacity by analyzing 1144 globally-distributed soil profiles. We show that current stocks total 899 Pg C to a depth of 1 m in non-permafrost mineral soils. Although this constitutes 66% and 70% of soil carbon in surface and deeper layers, respectively, it is only 42% and 21% of the mineralogical capacity. Regions under agricultural management and deeper soil layers show the largest undersaturation of mineral-associated carbon. Critically, the degree of undersaturation indicates sequestration efficiency over years to decades. We show that, across 103 carbon-accrual measurements spanning management interventions globally, soils furthest from their mineralogical capacity are more effective at accruing carbon; sequestration rates average 3-times higher in soils at one tenth of their capacity compared to soils at one half of their capacity. Our findings provide insights into the world’s soils, their capacity to store carbon, and priority regions and actions for soil carbon management. Mineral-organic associations play a key role in soil carbon preservation. Here, Georgiou et al. produce global estimates of mineral-associated soil carbon, providing insight into the world’s soils and their capacity to store carbon